ENGLISH TEACHERS’ READINESS IN DESIGNING LESSON PLAN BASED ON CURRICULUM MERDEKA AT VOCATIONAL SCHOOL NUMBER 1 JAMBI - Azizah, kharisma Nur (JR-ELT (Journal of Research in English Language Teaching), 2024)
This research, conducted by Kharisma Nur Azizah, explores the readiness of English teachers at SMKN 1 Kota Jambi in designing lesson plans based on the "Curriculum Merdeka." The study aims to identify the preparations and challenges faced by teachers in supporting their readiness for the 10th-grade lesson plans under this new curriculum framework. Utilizing a qualitative case study approach, the research collected data through interviews. The findings reveal several key aspects of readiness and challenges for English teachers. Readiness includes cognitive aspects such as the importance of lesson plan design, understanding the independent curriculum, using media resources to support lesson plan creation, and the ability to compile and evaluate lesson plans effectively. Physical readiness (energy and health), psychological readiness (interest and motivation), and the availability of supporting facilities and infrastructure are also critical components. The study found that the curriculum is both flexible and complex. Teachers utilize various media sources like ESP, TOEIC, the Merdeka teaching platform, and YouTube to prepare lesson plans based on major department profiles and determine competency (CP), topic (TP), and lesson activity plans (ATP). Physical readiness in designing lesson plans requires an intensive two-week period, while psychological readiness helps increase knowledge and update teaching experiences to meet student needs effectively.Challenges include time management and aligning lesson plans with diagnostic assessments of student characteristics to ensure they meet the standards of the Curriculum Merdeka.